Measurement of g factors in 84,86Zr and 87Nb by the recoil distance transient field γ-γ coincidence technique - Teich, C.; Jungclaus, Andrea; Fischer, V.; Kast, D.; Lieb, K. P.; Lingk, C.; Ender, C.; Härtlein, T.; Köck, F.; Schwalm, Dirk; Billowes, J.; Eberth, J.; et al. (Physical review. C, Nuclear physics, 1999)
Magnetic dipole moments of excited states in 84Zr and the N=46 isotones 86Zr and 87Nb were measured. The recoil distance transient field method, which is a coincidence technique combining the recoil distance and the transient field methods, was applied. The measurement was performed such that it was sensitive only to those excited states which were populated a few picoseconds after the nuclear reaction. The influence of unobserved continuum feeding on the measured precession angles can thus be neglected. The results are compared with the values obtained using other experimental techniques and with shell model calculations.
Gesehen am 30.11.2020
Im Titel sind "84", "86" und "87" hochgestellt